Social and Economic Impacts of Tourism Development on the Local Community of Kampung Pelangi, Semarang - Mendrofa, Herlinawati; Octafian, Ray (PT. Riset Press International, 2024)
The aim of this research is to explore and analyze the social and economic impacts of tourism development in Kampung Pelangi Semarang on the local community. The main research question to be answered in this study is: